Climate‐mediated shifts toward bunchgrass dominance 40 years after grazing cessation in Saguaro National Park, Arizona, USA. Issue 4 (16th December 2021) - Summers, Ryan; Hovland, Matthew; Gibson, Yvette; Mata‐González, Ricardo
Abstract: Questions: Vegetation transects were surveyed in Saguaro National Park, Arizona, in 1976 and 2007 as part of a grazing study. We resurveyed the same transects in 2018 and accessed fire and climate data in order to examine trends in plant community structure. We asked the question: has the plant community shifted in species' density, canopy cover and diversity in the past 40 years since grazing cessation? And if so, do these shifts favor a specific species, or plant functional guild? We also asked if climate and time since fire influenced plant community structure? Location: Saguaro National Park East is located in the Sonoran Desert and Madrean Sky Island ecoregion interface in Tucson, Arizona, United States. Methods: Plots (10) were 20 m × 50 m, with 21 20‐m transects within each plot used to gather plant canopy cover and density of perennial species with the line‐intercept method. Data were aggregated by plot and analyzed using generalized linear mixed‐effects modeling and non‐metric multi‐dimensional scaling. Results: Overall canopy cover, density, and Shannon diversity increased significantly between 1976 and 2018. Ferns, forbs, graminoids, subshrubs and vines increased significantly in cover and density between 1976 and 2018. Wildfire recency was significantly negatively correlated with forb density, and density or cover of five dominant species (mostly woody). Shifts in plant community structure between survey years was correlated with increased temperature, precipitation, and vapor pressure differential. Conclusion: After 40 years of grazing cessation, significant increases in herbaceous cover, and a lack of significant increase in woody encroachment are signs of recovery. Increases in temperature may be responsible for accelerating shifts to warm‐season species‐dominant communities. Fire was unexpectedly not a significant factor in plant community structure; however, park management will likely need to address increased wildfire risk given the increase in herbaceous cover and density. Abstract : Saguaro National Park, Arizona, USA, has excluded livestock grazing for the past 40 years. We found that, since then, plant communities have become more diverse, and less dominated by woody species. Shifts in plant communities appear to be driven by a combination of climate, fire, and grazing cessation, and may not always be desirable.